Lumped Parameter Modelling in Femoral Popliteal Artery for Normal and Severe Conditions - Kaha, Asrizan; Taib, ishkrizat; Paisal, Muhammad Sufyan Amir; Tajul Arifin, Ahmad Mubarak; Ismail, Al Emran; Asmuin, Norzelawati; Abdul Haq, Reazul Haq; Chatpun, Surapong; Yamamoto, Takahisa; Osman, Kahar (International Journal of Integrated Engineering, 2018)
Development of numerical technique would be benefited to diagnose the biological structure especially in femoropopliteal artery. Blood circulatory system and heart hemodynamic performance can be simulated by applying lumped parameter method. Thus, this study aims to develop numerical modelling in femoropopliteal artery by constructing an electric analog models to the system. Three different cases have been considered in this study; normal blood condition, aneurysm and atherosclerosis conditions. Normal blood condition is also analysed as a basis study of comparison between aneurysm and atherosclerosis conditions. The electrical analog model with 3 nodes and terminal load at the end of this model are proposed. This algorithm is then verified against numerical data simulated using commercial software.Â A linear analysis of this system, together with in rate waveform propagation obtains, shows that periodic mean pressures and flow distributions in large arteries are highly depend on vessel resistances and the compliances compared to the inertias of the system. The study shows that normal and abnormal conditions effect instantaneously to pressure and flow waveforms. The result shows that the highest peak pressure is shown in atherosclerosis condition whilst aneurysm condition shows the highest flow rate.